1980
DOI: 10.1055/s-2008-1074879
|View full text |Cite
|
Sign up to set email alerts
|

Rotenoids and 7,2,'4',5'-Tetramethoxyisoflavone in Amorpha fruticosa L. Fruits

Abstract: From the petrol-ether extract of ripe Amorpha fruticosa fruits two rotenoids and one isoflavone have been isolated. The ripe fruits of Amorpha fruticosa L. (Papilionaceae) contain glycerides and essential oil [I], the rotenoid glycoside amor~hine [2] and its analogous [3], as well as small amounts of 7,8-dehydroamorphygenine, amorphygenine, amorphygenol [3], 22,23-dihydroamorphygenine [4] and 6a,l2a-dehydro-a-toxycarol[5]. According to [5] this last compound is responsible for the insecticidal activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1982
1982
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The remaining known compounds were identified as 2-[( E )-styryl]-5-geranylresorcin-1-carboxylic acid ( 16 ), amorfrutin B ( 17 ), 2-carboxy-3,5-dihydroxy-4-geranylbibenzyl ( 18 ), 2-geranyl-5-[( Z )-styryl]­resorcin ( 19 ), amorphastilbol ( 20 ), 2-geranyl-5-(2-phenylethyl)­resorcin ( 21 ), amorfrutin A ( 22 ), xanthoangelol ( 23 ), sermundone ( 24 ), rot-2′-enonic acid ( 25 ), deguelin ( 26 ), α-toxicarol ( 27 ), 6a,12a-dehydrodeguelin ( 28 ), dalpanol ( 29 ), rotenone ( 30 ), dalbinol ( 31 ), hydroxy­amorphispironone ( 32 ), 6′- O -β- d -glucopyranosyl­dalpanol ( 33 ), daidzein, 5,7-dihydroxy-4′-methoxyisoflavone, 5-hydroxy-7,4′-dimethoxyisoflavone, afrormorsin, 7-hydroxy-2′,4′,5′-trimethoxy­isoflavone, 7,2′,4′,5′-tetramethoxy­isoflavone, munduserone, cis -12a-hydroxy­munduserone, 6-deoxyclitoriacetal, cis -12a-hydroxyrot-2′-enonic acid, sumatrolic acid, tephrosin, 11-hydroxytephrosin, 12a-hydroxydalpanol, rotenolone, 11-hydroxyrotenone, amorphigenin, amorphispironone, 11-licoagroside F, kaempferol 3- O -α- l -rhamnopyranosyl-(1→2)-β- d -glucopyranoside-7- O -α- l -rhamnopyranoside ( 13a ), and 6′- O -β- d -glucopyranosyl-12a-hydroxydalpanol ( 33a ) by comparison with the literature data.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining known compounds were identified as 2-[( E )-styryl]-5-geranylresorcin-1-carboxylic acid ( 16 ), amorfrutin B ( 17 ), 2-carboxy-3,5-dihydroxy-4-geranylbibenzyl ( 18 ), 2-geranyl-5-[( Z )-styryl]­resorcin ( 19 ), amorphastilbol ( 20 ), 2-geranyl-5-(2-phenylethyl)­resorcin ( 21 ), amorfrutin A ( 22 ), xanthoangelol ( 23 ), sermundone ( 24 ), rot-2′-enonic acid ( 25 ), deguelin ( 26 ), α-toxicarol ( 27 ), 6a,12a-dehydrodeguelin ( 28 ), dalpanol ( 29 ), rotenone ( 30 ), dalbinol ( 31 ), hydroxy­amorphispironone ( 32 ), 6′- O -β- d -glucopyranosyl­dalpanol ( 33 ), daidzein, 5,7-dihydroxy-4′-methoxyisoflavone, 5-hydroxy-7,4′-dimethoxyisoflavone, afrormorsin, 7-hydroxy-2′,4′,5′-trimethoxy­isoflavone, 7,2′,4′,5′-tetramethoxy­isoflavone, munduserone, cis -12a-hydroxy­munduserone, 6-deoxyclitoriacetal, cis -12a-hydroxyrot-2′-enonic acid, sumatrolic acid, tephrosin, 11-hydroxytephrosin, 12a-hydroxydalpanol, rotenolone, 11-hydroxyrotenone, amorphigenin, amorphispironone, 11-licoagroside F, kaempferol 3- O -α- l -rhamnopyranosyl-(1→2)-β- d -glucopyranoside-7- O -α- l -rhamnopyranoside ( 13a ), and 6′- O -β- d -glucopyranosyl-12a-hydroxydalpanol ( 33a ) by comparison with the literature data.…”
Section: Resultsmentioning
confidence: 99%
“…The species B could As a starting material which contains components with lower polarity, an industrial sample of "Absolute of Amorpha" (Pharmachim, Bulgaria) was used, produced by extraction of the ripe fruits with petrol. It was separated on a silica column with mixtures of chloroformether (1). For polar components, the ground fruits (2 kg) were extracted with chloroform-methanol 1: 1(3 x 1 000 ml).…”
Section: Resultsmentioning
confidence: 99%
“…Ginseng, the roots of Panax ginseng C. A. Meyer (Araliaceae), has been used in traditional Chinese medicine for treatment of various disorders for thousands of years (1,2). Recent studies showed the major active ingredients of ginseng to be a group of ginsenosides, and they are named ginsenoside R (x = a, b1, b2, c, d, e, g1 .…”
Section: Introductionmentioning
confidence: 99%
“…Another known rotenoid, 12aß-hydroxyamorphigenin [6], was first shown to exhibit extremely potent cytotoxicity (ED50 <0.001 µ-g/ml) in six neoplastic cell lines. In addition to these compounds, three isoflavones (afrormosin [1], 7,2',4',5'-tetramethoxyisoflavone [2], 8methylretusin [3]) and five rotenoids (amorphispironone [4], amorphigenin [5], dalpanol [7], 12aß-hyd oxydalpanol [8], and tephrosin [9]) were isolated. Compound 8 was isolated for the first time as a natural product from this plant.…”
mentioning
confidence: 99%